Application of the digital marketing ecosystem to MSME Batik Rajah, Magelang City - Marlina Kurnia; Tri Wahyu Handayani; Erika Putri Wijayanti; Ahmad Riyanto; Fajar Shidiq Hidayat; Reni Septiana (Community Empowerment, 2023)
This community service aims to overcome the problems of UKM Batik Rajah, Magelang City in terms of marketing, packaging, and financial records. The methods used are outreach, training, and mentoring. The result of this program is repackaging by changing product packaging to utilizing marketplaces and social media for product promotion and sales. With the consistent use of digital marketing, it is believed that the Batik Rajah market will expand so that it can improve people's welfare. In addition, MSMEs Batik Rajah have also updated their financial books so that they can simplify the process of estimating profit and loss and recording daily transactions